Targeting mitochondrial dynamics proteins for the treatment of doxorubicin-induced cardiotoxicity - Chen, Rui; Niu, Mengwen; Hu, Xin; He, Yuquan (Frontiers in Molecular Biosciences, 2023)
Doxorubicin (DOX) is an extensively used chemotherapeutic agent that can cause severe and frequent cardiotoxicity, which limits its clinical application. Although there have been extensive researches on the cardiotoxicity caused by DOX, there is still a lack of effective treatment. It is necessary to understand the molecular mechanism of DOX-induced cardiotoxicity and search for new therapeutic targets which do not sacrifice their anticancer effects. Mitochondria are considered to be the main target of cardiotoxicity caused by DOX. The imbalance of mitochondrial dynamics characterized by increased mitochondrial fission and inhibited mitochondrial fusion is often reported in DOX-induced cardiotoxicity, which can result in excessive ROS production, energy metabolism disorders, cell apoptosis, and various other problems. Also, mitochondrial dynamics disorder is related to tumorigenesis. Surprisingly, recent studies show that targeting mitochondrial dynamics proteins such as DRP1 and MFN2 can not only defend against DOX-induced cardiotoxicity but also enhance or not impair the anticancer effect. Herein, we summarize mitochondrial dynamics disorder in DOX-induced cardiac injury. Furthermore, we provide an overview of current pharmacological and non-pharmacological interventions targeting proteins involved in mitochondrial dynamics to alleviate cardiac damage caused by DOX.